The Effect of Transformational Leadership and Organizational Culture on Organizational Commitment Role of Mediation Empowerment Military of Kodim 0510/Tigaraksa, Tangerang - Wira Satria Dawy; Corry Yohana; Agus Widodo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine the effect of transformational leadership and organizational culture on organizational commitment by examining the mediation of empowering members at Kodim 0510/ Tigaraksa, Tangerang Regency. In total, 252 members completed an online questionnaire that assessed transformational leadership, organizational culture, empowerment, and organizational commitment. The organizational commitment model was tested using a structural equation model. The results showed that empowerment mediates the relationship between transformational leadership and organizational commitment, it also mediates the relationship between organizational culture and organizational commitment.